Smallholder dairy in Kenya - Ngigi, Margaret (International Food Policy Research Institute, 2004)
The author describes a successful case study as follows: "Dairy production in Kenya has grown at 2.8 percent per year over the past two decades, resulting in per capita production levels double those found anywhere else on the continent. Kenya's commercial farmers laid the foundation for this growth. They introduced improved dairy breeds in the early 1900s, and by the 1930s they had successfully lobbied for a range of government financial and policy support, including quarantine laws, veterinary laboratories, artificial insemination services, and marketing and price controls managed through the Kenya Cooperative Creameries.... Subsequent smallholder growth began slowly in the 1950s and 1960s, spurred by rapidly growing cash incomes in rural areas, which stimulated steadily rising demand for milk." The brief goes on to explore the impacts, the drivers of change, and the lessons learned for future successes. To illustrate her text, the author contrasts dairy sectors in Kenya, Ethiopia, and Uanda."